Satisfaction of Agricultural Information Service in Phra Nakhon Si Ayutthaya - Praepattarapisuth, Ladda; Prapin, Wittaya; Chodpan, Salaitip (Kasetsart Journal of Social Sciences, 2014)
The purposes of this study were to investigate the agriculturists’ satisfaction of receiving agricultural information. The samples were 400 agriculturists doing plantation in Phra Nakhon Si Ayutthaya. They were selected by using the purposive sampling. The multiple-choice and 5-rating-scale questionnaire were used to collect data. The statistics employed for analyzing the data were percentage and mean. It was found that 99 percent of the agriculturists agreed with a monthly distribution of the cartoon-version pamphlet of agricultural information service. Regarding the number of pamphlets received, nearly half of the agriculturalists (49.75%) received all 10 pamphlets distributed, followed by those who received 6-9 pamphlets (41.25%). Almost all of the agriculturists (99%) willingly continued receiving the pamphlets. Overall, the agriculturalists were highly satisfied with agricultural information conveyed in the pamphlets. When examined by education, age and main career of the agriculturalists, overall high satisfaction was also found. In addition, they were also highly satisfied with all response items, with an exception of the agriculturists who were under 25 years of age and those who did the gardening which were found to be moderately satisfied in certain aspects.